Incidence of c-Cbl mutations in human acute myeloid leukaemias in an Australian patient cohort - Ghassemifar, Reza; Thien, C.; Finlayson, J.; Joske, D.; Cull, G.; Augustson, B.; Langdon, W. (2011)
Aim: The aim of this study was to investigate the incidence and characteristics of c-Cbl mutations in acute myeloid leukaemias (AMLs) from an Australian patient cohort. Two initial studies examining c-Cbl mutations in AML, one from Germany and one from the US, found vastly different incidences of mutations (0.6% compared to 33%, respectively). Therefore, it was important to determine the incidence and characteristics of c-Cbl mutations in a cohort of Australian AML patients. Methods: Ninety patients with AML were investigated. The open reading frame between exons 4 and 11 of the c-Cbl gene was analysed by reverse-transcription polymerase chain reaction (RT-PCR), nested PCR and DNA sequencing. Results: We found four AML samples (4/90; 4.44%) with distinct c-Cbl deletions involving exons 6 to 9. Sample 10 [AML with t(8;21)] showed two deletions [c.870-1007del] and [c.1106-1228del]. Sample 81 (AML with minimal differentiation) showed a large deletion [c.1008-1431del] causing a frameshift and a premature stop codon. Sample 82 (AML without maturation) showed two deletions [c.928- 1307del] and [c.1385-1431del] also causing a frameshift and a premature stop codon. Sample 84 (AML with myelodysplasia related changes) showed a large deletion [c.964-1380del]. Conclusion: Although our data indicate that c-Cbl deletions are not common in AML in the Australian population, they do raise the possibility that c-Cbl mutations might contribute to the pathogenesis of these AML cases. © 2011 Royal College of Pathologists of Australasia.